Impaired telomere integrity and rRNA biogenesis in PARN‐deficient patients and knock‐out models. Issue 7 (6th June 2019) - Benyelles, Maname; Episkopou, Harikleia; O'Donohue, Marie‐Françoise; Kermasson, Laëtitia; Frange, Pierre; Poulain, Florian; Burcu Belen, Fatma; Polat, Meltem; Bole‐Feysot, Christine; Langa‐Vives, Francina; Gleizes, Pierre‐Emmanuel; de Villartay, Jean‐Pierre; et al.
Abstract: PARN, poly(A)‐specific ribonuclease, regulates the turnover of mRNAs and the maturation and stabilization of the h TR RNA component of telomerase. Biallelic PARN mutations were associated with Høyeraal–Hreidarsson (HH) syndrome, a rare telomere biology disorder that, because of its severity, is likely not exclusively due to h TR down‐regulation. Whether PARN deficiency was affecting the expression of telomere‐related genes was still unclear. Using cells from two unrelated HH individuals carrying novel PARN mutations and a human PARN knock‐out (KO) cell line with inducible PARN complementation, we found that PARN deficiency affects both telomere length and stability and down‐regulates the expression of TRF1, TRF2, TPP1, RAP1, and POT1 shelterin transcripts. Down‐regulation of dyskerin‐encoding DKC1 mRNA was also observed and found to result from p53 activation in PARN‐deficient cells. We further showed that PARN deficiency compromises ribosomal RNA biogenesis in patients' fibroblasts and cells from heterozygous Parn KO mice. Homozygous Parn KO however resulted in early embryonic lethality that was not overcome by p53 KO. Our results refine our knowledge on the pleiotropic cellular consequences of PARN deficiency. Synopsis: PARN deficiency impairs telomerase activity and causes telomere shortening and instability, together with defective ribosomal RNA biogenesis. The many functional consequences of PARN deficiency likely explain the clinical severity of Høyeraal‐Hreidarsson patients carrying biallelic PARN mutations. Steady‐state mRNA levels of several telomere‐related genes are reduced in PARN‐deficient cells. Telomere instability is induced by PARN deficiency. Down‐regulation of DKC1 mRNA in PARN‐deficient cells is due to p53 up‐regulation. Ribosomal RNA biogenesis is impaired in PARN‐deficient cells. Parn knock‐out mice are embryonic lethal and are not reverted by p53 knock‐out. Abstract : PARN deficiency impairs telomerase activity and causes telomere shortening and instability, together with defective ribosomal RNA biogenesis. The many functional consequences of PARN deficiency likely explain the clinical severity of Høyeraal‐Hreidarsson patients carrying biallelic PARN mutations.